Model Penjaminan Mutu Internal dalam Membangun Daya Saing Kampus Dakwah dan Peradaban (Study Exploratory Sequential Mixed Method di UIN Sayyid Ali Rahmatullah Tulungagung) - Lutfi, Farihul; Afifudin, Hanim (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Research Objectives: 1) To find out the internal quality assurance system policy in building the competitiveness of da'wah and civilization campuses; 2) To find out the internal quality assurance system in building the competitiveness of the da'wah and civilization campus. This study uses a mixed method (study exploratoy sequential mixed method) with a qualitative and quantitative approach. From the results of this study, the author concludes that: 1) The policy of the internal quality assurance system in building the competitiveness of the da'wah and civilization campus is implemented with the following substance: Determining the Standards of the Internal Quality Assurance System which is adjusted to the quality standards of higher education; Universities have adequate resources; University managers have high motivation to improve student achievement; Universities provide the best service for education customers; Higher education has strong leadership in resource management and quality services; Universities have a credible management system for education personnel; Universities have an Islamic culture that is conducive to educational customers; Universities have proud qualities along with the increase in the number of students; Universities carry out progressive educational innovations; Universities are able to achieve targets in accordance with the plan; 2) Quality Standards at Sayyid Ali Rahmatullah State Islamic University Tulungagung consist of five standards, namely Education Quality Standards, Research Quality Standards, Community Service Quality Standards, Cooperation Standards and Governance and Institutional Development Standards.